2017
DOI: 10.1038/srep46254
|View full text |Cite
|
Sign up to set email alerts
|

Four genes essential for recombination define GInts, a new type of mobile genomic island widespread in bacteria

Abstract: Integrases are a family of tyrosine recombinases that are highly abundant in bacterial genomes, actively disseminating adaptive characters such as pathogenicity determinants and antibiotics resistance. Using comparative genomics and functional assays, we identified a novel type of mobile genetic element, the GInt, in many diverse bacterial groups but not in archaea. Integrated as genomic islands, GInts show a tripartite structure consisting of the ginABCD operon, a cargo DNA region from 2.5 to at least 70 kb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…The metabolic islands may consume energy and compete with basal metabolism and the production process of secondary metabolites. In addition, metabolic regulation related genes have been found in certain GIs from bacteria [30]. The GIs deleted in this study may also contain non-essential and high energy-consuming metabolic pathways and certain negative regulatory factors related to PHA biosynthesis.…”
Section: The Improvement In the Pha Production Capacity Of The Mutantmentioning
confidence: 85%
“…The metabolic islands may consume energy and compete with basal metabolism and the production process of secondary metabolites. In addition, metabolic regulation related genes have been found in certain GIs from bacteria [30]. The GIs deleted in this study may also contain non-essential and high energy-consuming metabolic pathways and certain negative regulatory factors related to PHA biosynthesis.…”
Section: The Improvement In the Pha Production Capacity Of The Mutantmentioning
confidence: 85%
“…In addition, it is feared that because Psa has a high degree of genome plasticity, adaptive mutations may occur in destination countries, which may make the damage more severe. The many mobile genetic elements, such as genomic islands including IME and ICE, prophages, transposons and plasmids, which are present on the genomes of Psa could bring new features to Psa, leading to the introduction of environmental adaptability, such as drug resistance, and the acceleration of changes in pathogenicity/virulence (Sawada et al, 2002(Sawada et al, , 2014bGenka et al, 2006;Butler et al, 2013;McCann et al, 2013McCann et al, , 2017Fujikawa & Sawada, 2016Bardaji et al, 2017;Colombi et al, 2017;Vanneste, 2017). Each biovar has high homogeneity within the core genome, but when the information from the accessory genome is included in the phylogenomic analysis, a large diversity appears in each biovar, suggesting that Psa has been continuously accumulating insertion/ deletion and mutation events.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was experimentally confirmed that the ginABCD operon (Fig. c) containing three tyrosine recombinase genes is actually involved in the excision and insertion of the tox island (Bardaji et al ., ). It has already been revealed that genomic island‐like structures containing similar operons to the ginABCD operon are widely distributed in diverse bacteria (Genka et al ., ).…”
Section: Psa Biovars Found In Japan and Their Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations